2019
DOI: 10.1186/s12884-019-2217-7
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and psychometric evaluation of the breastfeeding self-efficacy scale to assess exclusive breastfeeding

Abstract: Background Increasing the prevalence of optimal breastfeeding practices, including exclusive breastfeeding for 6 months, could prevent an estimated 823,000 child deaths annually. Self-efficacy is an important determinant of breastfeeding behaviors. However, existing measures do not specifically assess exclusive breastfeeding self-efficacy, but rather self-efficacy for any breastfeeding. Hence, we sought to adapt and validate an instrument to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 55 publications
1
33
0
6
Order By: Relevance
“…7 BF also provides lifelong infant health benefits; the longer infants exclusively breastfeed, the greater benefit in reducing infantile and respiratory diseases (COVID- 19), sudden infant death syndrome, and chronic diseases related to obesity. [8][9][10][11][12] Ultimately, the public health burden of not BF results in a global gross expenditure of U.S. $341.3 billion, with $114.97 billion incurred by the North America Region. 13 The early cessation of BF (before 3 weeks) costs the United States an estimated $3.0 billion annually (2010 dollars) due to purchase of formula, increased infantile diseases and health visits, and lost wages ($2.3 billion being maternal costs).…”
Section: Introductionmentioning
confidence: 99%
“…7 BF also provides lifelong infant health benefits; the longer infants exclusively breastfeed, the greater benefit in reducing infantile and respiratory diseases (COVID- 19), sudden infant death syndrome, and chronic diseases related to obesity. [8][9][10][11][12] Ultimately, the public health burden of not BF results in a global gross expenditure of U.S. $341.3 billion, with $114.97 billion incurred by the North America Region. 13 The early cessation of BF (before 3 weeks) costs the United States an estimated $3.0 billion annually (2010 dollars) due to purchase of formula, increased infantile diseases and health visits, and lost wages ($2.3 billion being maternal costs).…”
Section: Introductionmentioning
confidence: 99%
“…It has been extensively used in studies among the general population of mothers or specific population groups; adolescents [24], primiparas [25][26][27], ethnic minorities [28][29][30], low income [31] and many more. Only recently, a 9-item exclusive breastfeeding specific selfefficacy scale was developed on the basis of Dennis BFSE-SF scale to assess EBF where breastfeeding is common, with very good psychometric properties [32]. Research evidence suggests a positive predictive association of breastfeeding self-efficacy and breastfeeding initiation, duration and exclusivity [17,18,20,[22][23][24]31].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the substantive benefits of optimal breastfeeding and the risks of non-exclusive breastfeeding, exclusive breastfeeding rates remain low (Boateng et al, 2019). A national survey from the Centers for Disease Control and Prevention (CDC, 2018) found that, in the United States, 83.2% of mothers start to breastfeed, and only 24.9% exclusively breastfeed through 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…There is a need to understand breastfeeding barriers in order to develop appropriate strategies to promote and support breastfeeding (Taha et al, 2018). Many determinants have been identified that deter breastfeeding behaviour (Boateng et al, 2019). Recent studies indicate that women who are depressed during pregnancy are more likely to discontinue breastfeeding than those with no depressive symptoms while pregnant (Amiel Castro et al, 2017; Tuthill et al, 2017).…”
Section: Introductionmentioning
confidence: 99%